(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Tourism education plays a major role in preparing students to gain professional and practical skills required by the tourism industry. Given that the tourism industry is a labor-intensive sector, it is undeniable that practical training is as important as theoretical training. In tourism education practical training is necessary for students to find the opportunity to apply what they have learned into practice and to develop personal skills and abilities.